Aislamiento de kaempferol del extracto de hojas de Senna reticulata e identificación por su caracterización fisicoquímica y espectroscopía UV/visible - Vergara Souza, Edilberto (2024)
Senna reticulata is an Amazonian plant of the Fabaceae family widely used in traditional medicine. The infusion of its flowers is used to treat inflammations liver diseases and stomach pains, while the leaves are used in the local treatment of cutaneous mycosis. The study aimed to isolate the compound kaempferol from the leaves of S. reticulata and to identify it by characterization of its physicochemical properties and spectroscopic analysis. The samples were collected in the hamlet of Ullpa Gallo, District of Belén, province of Maynas, Loreto Region, in the Peruvian Amazon. To isolate kaempferol, the procedure described by Domínguez Sepúlveda Xorge was used with a small modification. Yellow needle-shaped crystals were obtained with a yield of 0.475%, melting point of 278°C, and molecular weight of 286.02 g/mol. The hRf values in thin layer chromatography (TLC) in different solvents of resolution were: 39 in [toluene: chloroform: acetone], 20 in [benzene:butanone: methanol], and 8 in [water-butanone-methanol] respectively. The maximum absorption wavelengths in methanol were recorded at 266 and 367nm and in [methanol: acetic acid] solution at 274, 303, and 387nm, values similar to those reported in the literature. S. reticulata from the Peruvian Amazon could serve as a source of raw material to isolate kaempferol for medicinal purposes in phytotherapy and the pharmaceutical industry.